Wild plants and the food-medicine continuum-an ethnobotanical survey in Chapada Diamantina (Northeastern Brazil) - Patrícia Muniz de Medeiros; Karina Ferreira Figueiredo; Paulo Henrique Santos Gonçalves; Roberta de Almeida Caetano; Élida Monique da Costa Santos; Gabriela Maria Cota dos Santos; Déborah Monteiro Barbosa; Marcelo de Paula; Ana Maria Mapeli (BMC, 2021)
Abstract Background Ethnobotanical research has demonstrated that several wild food plants (WFP) are used for medicinal purposes. Therefore, in addition to constituting an important source of nutrients, WFP can be used to help treat and avoid health problems. This study sought to characterize the traditional use of plants considered simultaneously as food and medicine by local specialists in the community of Caeté-Açu, which borders Chapada Diamantina National Park (NE Brazil). We also sought to identify the variables that influence the species' cultural importance. Methods We selected local specialists based on a snowball sample and used a free-listing technique to register the wild plants they knew that are both edible and medicinal. Then, we asked the specialists to rank each plant component cited according to the following attributes: (1) ease of acquisition, (2) taste, (3) smell, (4) nutritional value, and (5) medicinal value. We used multiple regression to determine the variables that influence the cultural salience. Results The most culturally salient species was Anredera cordifolia (Ten.) Steenis. The main medicinal effects associated with this species were related to body strengthening, intestinal regulation, and stomach issues. The most salient used species were those that were easiest to acquire and had the highest perceived nutritional values. Conclusion It is likely that the sociocultural backgrounds of the respondents (elders, former miners, or descendants of miners) and the historical importance of wild food plants to local diets increased the predictive power of the perceived nutritional importance and ease of acquisition of these plants.